A multimodal discourse analysis of positioning and identity work in a leadership development practice.: A combined dialogicality and small story analysis - Bager, Ann Starbæk (Communication & Language at Work, 2019)
The paper shows an example of how interaction in a leadership development forum can be analyzed from a narrative-in-use perspective through a combined dialogicality and small story analysis strategy. This entails that a multimodal discourse analysis is conducted of the positioning and identity work accomplished in a research- and dialogue-based leadership development forum in a university setting. A micro-generic positioning analysis of the participants’ small story efforts is combined with an analysis of dialogicality involving other-orientation to show how storytelling takes place and how opposing discourses within organization and leadership studies co-emerge in multimodal interaction. Among other things the analysis shows how different sociomaterial interactional setups shape identity work in situ. The research contributes to the emerging study of organizational dialogical and narrative practices up close. It emphasizes both the broad (Discursive) and the local (discursive) dimensions together with sociomaterial aspects of discourse and storytelling, which are increasingly pursued and recommended within the fields of narrative, dialogue, and discourse studies.